Perceptions and needs of patients, caregivers and health professionals regarding an oncology community center: a qualitative study - Inbal Mitnik; Ilit Turgeman; Ilit Turgeman; Svetlana Baziliansky; Hassan Shalabna; Leena Nassar-Sakas; Gil Bar-Sela; Gil Bar-Sela (Frontiers in Public Health)
Introduction and aimsOncology community centers (OCCs) may be beneficial for patients residing in regions requiring prolonged travel to large hospitals. A new model of OCC has been established in a peripheral region of Northern Israel, in affiliation with a large hospital. This center aims to increase accessibility to medical care and to make it more patient centered. The current study aims to better understand the needs and perceptions of patients, caregivers, and health professionals regarding the OCC to integrate them into the newmodel OCC and adapt the medical services to the population’s needs.Materials and methodsSemi-structured interviews were conducted with 18 participants to explore their perceptions regarding the new OCC. The interviews were qualitatively analyzed using the interpretative phenomenological analysis method.ResultsPatients and caregivers recognized the advantages of receiving treatment closer to home but were concerned about losing their sense of security. Nurses expressed the need to increase their confidence by communicating closely with the hospital’s staff and ensuring safety in case of urgent situations. Physicians emphasized the importance of hospital and community collaboration and the potential to enhance treatment adherence.ConclusionThe results indicate that the new OCC was perceived as a significant step in developing medical services, however the main concern was a decrease in the level of confidence due to its distance from the hospital. Strong collaboration between academic and community settings is essential to ensure continuity of care and a sense of security.